A Multiteacher Preparation Program Study of Elementary Teacher Candidates' Self-Efficacy: Analysis of Participant Characteristics and Implications for Teacher Educators. Issue 3 (3rd July 2019) - Davis, Tammi R.; Bolyard, Chloé S.; (Scarlett) Zhang, Sijia; Livers, Stefanie D.; Sydnor, Jackie; Daley, Sharon
Abstract: The purpose of this cross-sectional study was to compare teacher candidates' sense of self-efficacy across institutions and at two different points within the teacher preparation program. Teacher candidate characteristics such as age and hometown were also explored in relation to reported levels of self-efficacy. Data in this study were collected from 143 teacher candidates enrolled at three Midwest institutions utilizing the Teachers' Sense of Efficacy Scale (TSES). Data analysis identified no statistically significant differences in teacher candidates' self-efficacy across three institutions, at two different points in the teacher preparation program, or based on age or hometown. Rasch results indicated that the TSES was invariant across age and teacher preparation programs. Implications for future research and teacher education are discussed.